EKONOMI POLITIK DAN REKONSTRUKSI IRAK - Sihbudi, Riza (Global: Jurnal Politik Internasional, 2004)
The plan for Iraqi reconstruction was formulated long time prior to the US-led coalition invasion in Iraq. Initial estimates place the cost of reconstruction (and the costs of maintaining a military presence) in Iraq to be anywhere between $100 billion and $500 billion, although the ultimate costs on the amount of time and number of US personnel stationed there. So, the Iraqi reconstruction is the most US ambitious project since the Second World War. Reconstruction is being managed by USAID under the control of the Pentagon, rather than the USAID normal operations supervised by the Department of State. In other words, the Pentagon that was dominated by the so-called Zionist mafia controlled both the invasion and the reconstruction. will depend As D. Albert Pastore stated, the Pentagon is under the control of a hard core group of Zionist Mafia led by "the gang of 3" that is Richard Perle, Paul Wolfowitz, and Douglas Feith. Therefore, the Iraqi reconstruction is a planning which does not serve the basic interest in the long run of the American nation. It serves the imperialistic interest of Israel and the Zionist groups --who now have a great say in the US policy under the President George Bush --to realize their dream of "the Great Israel". W.